Wireless gas leakage detection system using microcontroller and GSM SIM900: article - Aibeni, Aaina Diyana Hazwani (2013)
Gas leakage can be dangerous to the human by explosion, fire and asphyxiant. In chemical laboratory, gas leakage can harm the people in the area. However, there is no gas leakage detection system for chemical laboratory. The need of efficient gas leakage detection system in laboratory is important to avoid the dangerous situation to the people. In this paper, a wireless gas leakage detection system is developed to be applied in the chemical laboratory. The methane and butane gas were used in this project to test the system. The developed system consists of three main parts. It is Arduino Uno R3, MQ-9 gas sensor and alert system. The alert system consists of buzzer, DC fan and GSM Shield. The system is implemented in Arduino environment using C programming. Arduino and gas sensor is used to detect the gas leakage of natural gas. Conductivity level for gas sensor is standardized at resolution of 45. The detection starts when sensor read the changes of conductivity gas and trigger the buzzer and fan when exceed the reference value. Then, system simultaneously sends the alert message to inform the technician about the leaks of gas. In this project, the output voltage is representing the changes of concentration and conductivity level of gas. The system is successfully implemented and achieved the objective of the project.